Management options and long-term follow-ups for permanent double incisors: six to eleven-year case reports - Betül Şen Yavuz; Batın Ilgıt Sezgin; Barhan Pekel; Bora Korkut; Ali Menteş (BMC, 2024)
Abstract Background Double teeth are dental anomalies that can lead to aesthetic and orthodontic problems. Case presentation This report discusses two cases involving the multidisciplinary management of permanent maxillary left lateral incisors fused with a supernumerary tooth in two girls aged 9 and 10. Following intraoral and radiographic examinations, one was diagnosed with fusion, and the other was diagnosed with concrescence. The crown of the fused incisor was separated using a burs and extracted intraorally. The concrescent incisor was separated along its length using a laser and intentionally replanted extraorally. After a 6-year follow-up, no pathological signs were observed in the fused incisor. However, after an 11-year follow-up, external resorption was observed in the concrescent incisor. Conclusions Both incisors remained asymptomatic throughout the observation period. This case report highlights two different and effective methods employed to preserve the natural function, form, and aesthetics of double incisors.